Current status of CO2 capture with ionic liquids: Development and progress. (15th July 2023) - Faisal Elmobarak, Wamda; Almomani, Fares; Tawalbeh, Muhammad; Al-Othman, Amani; Martis, Remston; Rasool, Kashif
Highlights: Ionic liquids (ILs) are promising technique for CO2 capturing ( CAP CO 2 ) from flue gas. CAP CO 2 process mechanisms, challenges, biodegradability, and toxicity are highlighted. Impacts of cations/anions and ILs functional groups on CO2 uptake were presented. Selectivity of ILs to CO2 is higher than H2, N2, O2 and comparable with SO2 and H2 S. FUN-AILs + amine achieved 1:1 reaction stoichiometry higher than CO2 –amine process. Abstract: Global warming triggered by greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2), significantly influences climate change and has become a common environmental issue recently. The current amine-based technologies (ABTs) for CO2 capture ( CAP CO 2 ) have high energy demand, low absorption, and desorption rates, and are less environmentally sustainable due to high emissions of volatile solvents. Therefore, the development of environmentally friendly CAP CO 2 materials and/or processes is a growing area of research. The utilization of ionic liquids (ILs) for CAP CO 2 has recently attracted attention. The unique characteristics of ILs, such as their low vapor pressure and high affinity for CAP CO 2 as well as their low volatility make them a viable substitute for the existing processes. This work provides a comprehensive overview of the accomplishments and challenges during the use of ILs for CAP CO 2 . The Review also outlines the mechanisms of the CAP CO 2 with ILs at the molecular level, the properties of ILs, characterization of the CO2 /IL systems, and the effect of operating conditions on CO2 uptake ( U P CO 2 ) capacity by ILs. It also emphasizes the impact of cations, anions, and functional groups on the solubility of CO2 (( S CO 2 ) ) in ILs as well as the biodegradability and toxicity of ILs. Additionally, recent advances in IL membrane technology for the CAP CO 2 processes are considered. Lastly, the contribution of molecular simulations to create and assess ILs was reviewed. Protic and aprotic ILs properties have shown outstanding efficiency of U P CO 2 . The interactions between the anionic part of IL and CO2 enhance the U P CO 2 and outperform the efficiency of traditional organic solvents. Functionalized ionic liquids (FUNILs ) with tuned functional groups, supported ionic liquids membranes (SILMs) as well as reversible ionic liquids (RILs) have improved the efficiency of ILs as a promising CO2 capturing process from industrial streams even under low CO2 partial pressure. The relative importance of the chemical breakdown of the IL constituents (cation–anion interfacial structuring) during the CAP CO 2 process at different operating temperatures is unclear, and more research in this area is required to better inform the design of new ILs. This review provides a proper/systematic guideline to help ILs manufacturers and engineers design high-capacity ILs for appropriate CAP CO 2 .